The post-pandemic architectural treatment in Taipei: a “postcolonial-urban” complex - Lin, Francis Chia Hui (Journal of Asian architecture and building engineering, 2025)
The relief from the COVID-19 pandemic today is globally phenomenal. However, its architectural representation still suggests dramatic variables caused by different localities. Conspicuously, the imposition of social distancing has been displayed very differently in different places upon architectural treatment. This paper argues that such a built scenario can be understood through a theorisation of a “postcolonial-urban complex” that integrates architecture’s inevitable engagement in the discourses of form and knowledge and the postcolonial values registered in spatial signification. The postcolonial-urban complex refers to a series of leads to a subject position of the post-pandemic-built environment, including a sense of counter-dualism, the dynamics of domination and the reified subjectivation. Existing scholarship of architectural and urban studies hence needs a thorough re-examination into the epistemic suitability for responding the immediate historicity. This paper argues that such a demand has become sensible from the recent situation of Asia and its architecture and urbanism – the engagement of some Asian metropolitan areas in shaping ephemeral and micro-geopolitical forms reacting to the limits caused by social distancing give evidence. To further consolidate such argumentation, this paper intends to examine semiotically and empirically the post-pandemic architectural treatment in Taipei, Taiwan, as a preliminary yet critical pilot study.